2019
DOI: 10.1002/eco.2163
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of hydrologic variations for spatial distribution of fish assemblage in a large subtropical temperate river

Abstract: This study examines the effects of the flow and flood pulses on spatial dispersion of fish assemblages in the floodplain of the Paraná River in Argentina. We tested the hypothesis that high water levels and greater lateral connectivity promote fish dispersal and spatial homogenization of assemblage structure. We sampled four sites during different phases of the annual hydrologic cycle from 2010 to 2016. Water surface in the area was estimated during each phase. We computed multivariate statistics and estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…These changes associated with hydrology and channel material components have been widely studied by Amsler et al (2005), Pereira (2016), Ramonell et al (2000), Ramonell (2021), and Sobrero et al (2014). The area of a water body is a classical hydrological parameter used in flood hazard studies and in delimitating an area vulnerable to a given event (Cheng et al, 2021; Espínola et al, 2020), showing the absolute value of the flooded area. In general terms, the larger the area covered by water, the more dangerous the flood event is.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes associated with hydrology and channel material components have been widely studied by Amsler et al (2005), Pereira (2016), Ramonell et al (2000), Ramonell (2021), and Sobrero et al (2014). The area of a water body is a classical hydrological parameter used in flood hazard studies and in delimitating an area vulnerable to a given event (Cheng et al, 2021; Espínola et al, 2020), showing the absolute value of the flooded area. In general terms, the larger the area covered by water, the more dangerous the flood event is.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be relatively similar over large floodplain areas. For example, an overflow level of 4.5 m and an isolation level of 2.3 m (according to the Santa Fe gauging station) were estimated for a large portion of the South section of the MPR (Abrial et al, 2021; Espínola et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these high‐flow event relationships are also dependent on the scale of observations. Espínola et al (2020) found flooding increased the spatial variability of fish assemblages at the reach scale.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the ecological integrity and connectivity of dam-free river basins is crucial for minimizing the expected trend of biotic homogenization (Marques et al, 2018), especially across floodplains that depend on high flow pulses to increase the spatial variability and recruitment of fish assemblages (Cruz et al, 2020;Espínola et al, 2020). Pristine river basins can contribute significantly to the conservation of fish diversity in areas already impacted by dams (Marques et al, 2018;Silva et al, 2017Silva et al, , 2019Vasconcelos et al, 2021) or by several other human activities (Garcia et al, 2021).…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%